Analisis bioekonomi pemanfaatan sumberdaya ikan kakap di Kabupaten Kutai Timur: Bio-economic analysis of blood snaper resources utilization in Kutai Timur Regency - Erwan Sulistianto (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
The aims of this research was to estimate the amount of fishing production and the number of fishing effort that can provide optimal benefits in economically and biologically. This study uses Algorithm Fox Models bioeconomics. The result showed that the blood snaper fishing activities in Waters Kutai Timur is overfishing, because the value of h (112.00 tons), E (1,051 trips), π (Rp2,657.10 million) on the actual in greater than the MEY (h = 13.27 tons, E = 479 trips, π = Rp285.02 million).